Causal Parameters and Policy Analysis in Economics: A Twentieth Century Retrospective* - Heckman, James J. (Quarterly Journal of Economics, 2000)
The major contributions of twentieth century econometrics to knowledge were the definition of causal parameters within well-defined economic models in which agents are constrained by resources and markets and causes are interrelated, the analysis of what is required to recover causal parameters from data (the identification problem), and clarification of the role of causal parameters in policy evaluation and in forecasting the effects of policies never previously experienced. This paper summarizes the development ofthese ideas by the Cowles Commission, the response to their work by structural econometricians and VAR econometricians, and the response to structural and VAR econometrics by calibrators, advocates of natural and social experiments, and by nonparametric econometricians and statisticians.